Ethanolic extract of Mucuna pruriens leaves ameliorates carbon tetrachloride and rifampicin-induced hepatotoxicity and nephrotoxicity in wistar albino rat - Temidayo Ogunmoyole; Ayomide Micheal Ola-Awe; Omotola Grace Fatile (BMC, 2021)
Abstract Background Mucuna pruriens (L.) has been used for the treatment of several ailments in folkloric medicine. The present study therefore investigates the hepatoprotective and nephroprotective potentials of its leaves extract with a view to providing a potent alternative in the management of liver and kidney diseases. Methodology Forty male albino rats were randomly placed into eight groups comprising five animals each. Animals in group I were administered with the distilled water, while groups II and VI were exposed to CCl4 and rifampicin respectively. Animals in groups III and IV were initially exposed CCl4 and treated with 50 and 100 mg/kg bw M. pruriens respectively. Similarly, groups VII and VIII animals were exposed to rifampicin and treated with 50 and 100 mg/kg bw M. pruriens respectively. Animals in group V were treated with 100 mg/kg bw silymarin by oral gavage after an initial exposure to CCl4. Selected biomarkers of liver and kidney damage were determined in the serum and organs homogenate. Liver and kidney slices of experimental animals were also stained for histopathological examination. Results Exposure to CCl4 and rifampicin respectively resulted in marked distortion in lipid profile, inhibition of antioxidant enzymes and a surge in ALT, AST, ALP, urea, uric acid, bilirubin and creatine kinase. Treatment with M. pruriens extract reversed all deranged biochemical and histopathological parameters in a dose-dependent manner. Conclusion Extract of M. pruriens leaves restored deranged biochemical and histopathological parameters in the liver and kidney with similar potency to silymarin. Hence, leaf extract of M. pruriens is a potential hepatoprotective and nephroprotective agent that can be exploited in the management of liver and kidney diseases.